Central nervous system disease with JC virus infection in adults with congenital HIV. (2nd February 2021) - McEntire, Caleb R.S.; Fong, Kathryn T.; Jia, Dan Tong; Cooper, Ellen R.; Cervantes-Arslanian, Anna M.; Mateen, Farrah J.; Anand, Pria; Thakur, Kiran T.
Abstract : Objective: The aim of this study was to describe the natural history of individuals with congenital HIV who develop JC virus (JCV) infection of the central nervous system (CNS). Methods: We retrospectively evaluated individuals with congenital HIV who met criteria for progressive multifocal leukoencephalopathy (PML) or JCV granule cell neuronopathy (JCV GCN) at three major healthcare centres in the northeast USA. Data on adherence to combined antiretroviral therapy (cART), neurologic symptoms, serum markers of immunity and HIV infection, cerebrospinal fluid (CSF) analyses, radiographic features, modified Rankin Scale (mRS) scores and survival were collected from the electronic medical record up to a censoring date of 1 August 2020. Results: Among 10 adults with congenitally acquired HIV, nine were diagnosed with definitive PML and one was diagnosed with probable JCV GCN. Individuals presented at the time of their PML or JCV GCN diagnosis with a mean mRS of 2.0 (standard deviation 1.0). A premorbid mRS was documented for six patients and was zero in all cases. The most common risk factor was confirmed cART nonadherence in nine individuals. Five individuals with PML and one with JCV GCN died, with a latency from symptom onset to death of approximately 3 months for three individuals, and approximately 2 years for the remaining two. Conclusion: Youth-adulthood transition is a high-risk point for dropping off from medical care. The study of this timepoint in people living with HIV could help inform effective care in these individuals.